Crystallographic and theoretical studies on a coupled chain of AF binuclear Cu(II)-fluoraspirinate complexes - Lamas, Carlos Alberto (2008)
We present here the low temperature (116K) crystal and molecular structure of poly-[μ-pyrazine{tetrakis-fluoraspirinate-dicopper(II)}]diacetonitrile, for short [Cu(Fasp)4Cu(pyz)]n, a 5-halogenated derivative of pharmacologically relevant copper aspirinates. We also discuss the theoretically expected magnetic and thermodynamic behavior of this interesting system for molecular magnetism.